Association between BDNF Val66Met polymorphism and generalized anxiety disorder and clinical characteristics in a Mexican population: A case–control study. Issue 11 (March 2019) - González-Castro, Thelma Beatriz; Pool-García, Sherezada; Tovilla-Zárate, Carlos Alfonso; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Frésan, Ana; Genis-Mendoza, Alma Delia; Pérez-Hernández, Nonanzit; Nicolini, Humberto
Abstract : Abstract: The aim of the present case–control study was to explore the association between BDNF Val66Met (rs6265) polymorphism and generalized anxiety disorder in Mexican individuals, and whether this polymorphism plays a role in the symptomatology of anxiety. A total of 212 subjects were included in the study. Around 75 patients with generalized anxiety disorder were diagnosed by psychiatrists based on the DSM-IV instrument and 137 unrelated subjects psychiatrically healthy were used as comparison group. The subclinical symptomatology in patients was assessed with the State-Trait Anxiety Inventory. BDNF rs6265 genotypes were analyzed using the polymerase chain reaction end-point method. The association between BDNF Val66Met with the risk for generalized anxiety disorder was evaluated using 4 inheritance models. The present study showed that carrying the Met allele confers increased risk for the presence of generalized anxiety disorder (χ 2 = 4.7, P = .03; OR (95%) 1.96 (1.05–3.56)) when patients with generalized anxiety disorder were compared with the comparison group. Our results provide evidence of an association between the Val66Met polymorphism of the BDNF gene and generalized anxiety disorder in a Mexican population. However, no association was observed between this polymorphism and the symptomatology of anxiety.